Incidental prostate cancer in patients undergoing radical cystoprostatectomy in treatment for bladder cancer: our five-year results - Saidi, Skender; Stavridis, Sotir; Dohchev, S; Stankov, Oliver; Komina, Selim; Petrushevska, Gordana; Popov, Z (SHMSHM - AAMD, 2013)
The aim of the paper was to verify the incidence and features of incidental prostate cancer in patients who underwent radical cystoprostatectomy for invasive bladder cancer. Methods and results: A total of 96 patients underwent radical cystoprostatectomy between January 2006 and December 2010 in the University Clinic of Urology in Skopje. 10 patients were excluded for incomplete data. The average age of the study group was 61.2 years (range 32-78). Prostate cancer was found in 10 (11.6%) cases. Seven patients were clinically insignificant. Conclusion: Incidentally diagnosed prostate cancer was frequently insignificant. Digital rectal examination and prostate specific antigen should be part of the diagnostic procedure in patients who undergo cystoprostatectomy. Standard RCP which include removal of bladder with prostate gland and seminal vesicles is safer for radicality and prevention of residual prostate cancer.
Keywords: bladder cancer; cystoprostatectomy; prostate cancer